Undescribed alkyne-geranylcyclohexenetriols from the endophyte Diaporthe caulivora 09F0132 and their anti-melanogenic activity. (October 2022) - Yang, Shuen-Shin; Chen, Yih-Fung; Ko, Horng-Huey; Wu, Ho-Cheng; Hsieh, Sung-Yuan; Wu, Ming-Der; Cheng, Ming-Jen; Chang, Hsun-Shuo
Abstract: To explore valuable endophytic fungus from Formosan Lauraceous plants as natural medicinal products, the fungus, Diaporthe caulivora isolated from leaves of Neolitsea daibuensis, was investigated. Through a thorough investigation of the ethanolic extract of the solid fermentation of D. caulivora 09F0132, six undescribed alkyne-geranylcyclohexenetriols, caulivotrioloxins A–F, one undescribed trichopyrone, diapopyrone, two undescribed sesquiterpenes, caulibysins A-B, one compound firstly isolated from the natural source, 3- O -desmethyl phomentrioloxin, and eight known compounds have been successfully identified. The absolute configuration of caulibysin A was confirmed by single-crystal X-ray diffraction, and those of (3 R, 8 S )-5, 7-dihydroxy-3-(1-hydroxyethyl)phthalide and (3 S, 8 S )-5, 7-dihydroxy-3-(1-hydroxyethyl)phthalide were determined by circular dichroism (CD) spectra. Among the isolated compounds, caulivotrioloxin A concentration-dependently decreased the cellular melanin contents and tyrosinase activities in mouse melanoma B16–F10 cells, suggesting the anti-melanogenic potentials. The anti-melanogenic effects of caulivotrioloxin A involved the decrease in the protein expressions of melanogenic enzymes, including tyrosinase, tyrosinase-related protein (TRP)-1, and TRP-2. Taken together, these results suggested that the isolates from D. caulivora could be served as natural melanogenesis inhibitors for cosmeceutical applications. Graphical abstract: Image 1 Highlights: 18 Compounds including nine undescribed compounds were isolated from D. caulivora. The absolute configurations of compounds were determined by X-ray and CD spectra. Caulivotrioloxin A exhibited skin-lightning activity. This is the first study of alkyne-geranylcyclohexenetriols' skin-lightning effects.